Phytochemical and biological studies on piper sarmentosum - Kuan, Sing Wei. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Phytochemical and biological studies have been carried out on the leaves of Piper sarmenlOsum. The extracts were subjected to thin layer chromatography, column chromatography and preparative thin layer chromatography in order to isolate and purify pure compounds. Two semi pure compounds with the molecular weight of 208 and 270 were isolated. These compounds showed the Rf values of 0.6 and 0.9 in hexane-acetone (7:3). The mass spectra of MA08A and MA09A showed similarity to standard mass spectra of isoasarone. Based on the mass spectra and infra red (IR) information, compound MA09~ most probably be isoasarone. In the toxicity test, most of the fractions and crude extracts indicated a low toxicity on the larvae of Artemia salina. Only fractions MA03 and MA09 showed LDso at 10 !lglmL, while for fractions MA04 and MA08, the LDso value was 55 !lglmL and 40 \.lglmL respectively